Colour design preference framework for attracting Middle Eastern tourists to hotel lobbies in Malaysia - Al Zoubi, Mohammad Kamal Hussein (2020)
Malaysia faced an average drop of 5.2% tourists from Middle Eastern countries during the period 2014-18, which in turn affected the annual income of RM84.14 billion. In this regard, the present research aims at documenting the colour design principles in hotel lobbies of Malaysia. Further, it also aims at analysing the colour effects in interior design and finally, the purpose is to develop a colour preferences framework that attracts Middle Eastern tourists towards Malaysian hotel lobbies. Moreover, the study is aimed to compare the results of Middle Eastern tourists’ colour palette preferences with that of four other cultures such as American, English, Japanese, and Koreans (Park and Guerin, 2002). At first, the literature review covered Malaysian hospitality facilities, colour design psychology, colour preferences of interior design, and colour design environment. Under each theme, a review of major works by different scholars was performed to critically analyse their contributions towards future investigations and aspects that need to be enhanced for the colour psychology. Then, the study used survey methodology to determine the expected psychological effects of colours in interior design. An integrated colour palette was applied to assist in identifying the differences on colour meaning and colour preferences in interior environments for Middle Eastern tourists who visit Malaysia. The images of four interior colour palettes were shown to Middle Eastern tourists at random afterwhich they were requested to complete a questionnaire. A total of 14 descriptor words such as pleasant, calming, expensive, open, spacious, intricate, inviting, comfortable, modest, ordered, sophisticated, coordinated, unified or rich were identified to reflect the colour preference and meaning for the respective respondent. In this respect, the results of the study included the documentation of colour principles with regards to interior design in Malaysian hotel lobbies, understanding the colour effects in interior design elements, and the development of ‘colour preferences framework’ targeting Middle Eastern tourists. The results of the study focusing Middle Eastern tourists’ colour preferences and its meaning showed that the most preferred and meaningful colour palette was B. The colours of this palette were selected from the Grand Millennium Hotel. However, it also indicates that the Middle Eastern tourists preferred an ‘open’ and ‘inviting’ colour environment as well as a ‘coordinated’, ‘ordered’, and ‘sophisticated’ environment. These colours are presented by warm hues (79.9%), light value (59.2%), Medium chroma (44.9%), low-value contrast (4.5/5.4), and medium chroma contrast (10.3/10.1) characteristics. In comparison with the selected four cultures, Middle Easterners’ colour characteristics were found to be similar alike Americans though they differ much from English, Japanese and Korean cultures. Besides guiding interior designers from different cultures to design the built environment for other cultures, this study is significant in supporting the development of tourism sector in Malaysia. The results will also help hotel owners and operators in different cultural contexts for making affordable changes in their hospitality facilities, due to influx of seasonal tourism activities. Finally, the results of this study are significant to guide interior designers in designing culture-based environment in hotel lobbies. Notwithstanding, further studies could investigate and collect more information regarding Middle Eastern colour preferences in different areas, for instance, hotel rooms.